Pelaksanaan discharge planning pada pasien diabetes melitus: Studi literatur - Linda Yulia; Tuti Pahria; Sandra Pebrianti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Discharge planning from hospital to home among patients with diabetes mellitus: A literature studyBackground: Several studies have stated that patients with diabetes mellitus who do not get proper management when discharge after hospitalization are very at risk to readmission because of complications. Properly discharge planning programme is very essentials to reduce the number of readmission and following by controlled on patient's conditions. However, the fruitfulness level of discharge planning program in each hospital was different. planning in DM patients is still not optimal and does not explain in detail the discharge planning stages. Purpose: To determine several studies of discharge planning programme among patients with diabetes mellitus in several hospitalMethod: Literature study method with narrative review approach. Search for articles using databases by Science Direct, Pubmed and Google Scholar by entering keywords